How sexuality education programs have been evaluated in low-and lower-middle-income countries? - Ivanova, Olena (2020)
Background: Complex sexual and reproductive health interventions, such as sexuality education (SE), contain multiple components and activities, which often requires a comprehensive evaluation design and adaptation to a specific context. In this review, we synthetize available scientific literature on types of evaluation designs used for SE programs in low-and lower-middle-income countries. Methods: Two databases yielded 455 publications, from which 20 articles met the inclusion criteria. Narrative synthesis was used to summarize the findings. Evaluation approaches were compared to recommended evaluation frameworks. The quality of articles was assessed by using MMAT 2018. Results: A total of 15 interventions employed in 10 countries were evaluated in the 20 selected articles, with the quality of publications being moderate to high. Randomized controlled trial was the predominant study design, followed by quasi-experimental design. There were seven process evaluation studies, using mixed methods. Main outcomes reported were of public health or behavioral nature—condom use, sexual debut or delay, and number of sexual partners. By comparing evaluation designs to recommended frameworks, few studies fulfilled at least half of the criteria. Conclusions: Evaluations of SE are largely dominated by quantitative (quasi-)experimental designs and use of public health outcomes. To improve understanding of SE program effectiveness, it is important to assess the quality of the program development, its implementation, and its impact, using existing evaluation frameworks and recommendations.